A Survey on Wireless Communication Technologies and Standards - Gupta, Amit; Bisen, Dhananjay (International Journal of Computer Sciences and Engineering, 2015)
Communication is a process through which humans can exchange views, ideas, information etc. They use different languages and signs to communicate with each other. Over last decade humans live in a digital age where information is everything and communication can take place even from long geographical distances. The computer systems need some sort of platform and standards through which data and information can be communicated to each other. In this paper the advantages and drawbacks of communication in wired and wireless transmission media has been discussed. Then different types of wireless communication technologies with their features and drawbacks have been figure out. Finally the comparison between different wireless communication technologies standards has been summarized.